The potency of water leaves extract of bay (Syzygium polyanthum) and papaya (Carica papaya) as larvacides to filaria vector Culex queinquefasciatus (Diptera: Culicidae) - Vella Rohmayani; Anindita Riesti Retno Arimurti; Rinza Rahmawati Samsudin (Bioma : Jurnal Ilmiah Biologi, 2022)
Culex quenquefasciatus is a mosquito that acts as a vector of filariasis disease. In Indonesia filariasis is still one of the endemic diseases. This proves that the handling of vector Culex quenquefasciatus is still not done optimally. One way that can be done to control mosquito vectors one of them is to use larvacide. Larvacide which is widely used today is still synthetic. Although very efficient in causing mosquito mortality, larvacide synthesis harms the environment and can cause vectors resistance. Then another larvacide alternative is needed that is effective and does not cause negative effects. Plants can be a choice of larvacide from nature. The study aims to find out the potential of the water extract of bay leaves and papaya leaves in killing the larvae of the Cx. quenquefasciatus mosquito as well as the value of LC50 after 24-hour observation. The type of research used is experimental research. The concentration of the water extract of bay leaves and papaya leaves used is 10%, 30%, 50%, 70%, and 90% with trhee times replication. LC50 is calculated using the Finney formula (1971), the calculation is carried out using application SPSS statistical version 26. Based on the research conducted, the value of bay leaf water extract LC50 = 62.89 g/ml and papaya leaf water extract LC50 = 45.10 g/ml. So based on the LC50 value, ita can be concluded that papaya leaf water extract is more effective in causing mortality Cx. quenquefasciatus compared with bay leaf water extract.